Medical Committe for Jane Tolmach letter (1976)
This campaign letter from the Medical Committee for Jane Tolmach urges colleagues to support her Assembly candidacy instead of electing another lawyer to Sacramento. It argues that lawyers already dominate government and have shaped generous pensions, salaries, and liability laws that benefit their profession, sometimes at public expense. The letter portrays Tolmach as a respected, nonpartisan public servant admired across party lines and better suited to represent community interests. It asks for financial contributions, noting that a portion of political donations is tax-deductible, and frames support for Tolmach as an investment in good government.